GeoloGIS-BH: An Information System for Using the Built Heritage for Geological Teaching - C. Alves; Vitor Ribeiro; Marta Cunha; Paula Pereira; Cláudia Pinto (Lectito Journals, 2016)
There are examples of using stones of the cultural heritage for teaching purposes. Information systems have found several potential uses in the promotion and preservation of cultural heritage. In this paper is considered the conceptual framework of an information system concerning features of geological interest (FGI) in the built heritage (without any consideration in terms of its software implementation). This FGI concept is used here in a very wide sense to encompass characteristics of geological materials that can be recognized with the naked eye and analogies of geological processes in the built environment. Two perspectives are considered for information organization: occurrences of FGIs in the built heritage (more suitable for Earth Sciences teaching) and FGIs as components of built heritage elements (more suitable for humanities teaching). The main issue that arises from the ensuing discussion was found to be the findability of a given FGI, depending on its visual contrast and the characteristics of the built heritage element. It is argued that, in this way, geological concepts can contribute to the promotion and conservation of the built heritage.